2001
DOI: 10.1007/s100380170125
|View full text |Cite
|
Sign up to set email alerts
|

α-1-Antichymotrypsin gene A1252G variant (ACT Isehara-1) is associated with a lacunar type of ischemic cerebrovascular disease

Abstract: α-1-Antichymotrypsin (ACT) is a plasma protease inhibitor belonging to the serpine superfamily; it has many functions, and thus qualitative change in ACT is likely to result in specific diseases. We previously reported a variant AACT (ACT Isehara-1, Met389Val, A1252G) in patients with ischemic cerebrovascular disease (CVD). The present study was designed to examine the association of the variant with ischemic CVD, in 87 patients and 397 agematched controls. We found that the frequency of the A1252G variant (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Only the intron 4ab genotype of the eNOS gene was associated with isolated lacunar infarction and the AGT-20C allele may be a risk factor for leukoaraiosis [24,25,26,27]. Other studies have reported a strong association of the angiotensin-converting-enzyme genotype to lacunar stroke [28, 29] as well as a –174G/C polymorphism of interleukin 6 [30, 31] and a gene variant of α 1 -antichymotrypsin – a plasma protease inhibitor [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Only the intron 4ab genotype of the eNOS gene was associated with isolated lacunar infarction and the AGT-20C allele may be a risk factor for leukoaraiosis [24,25,26,27]. Other studies have reported a strong association of the angiotensin-converting-enzyme genotype to lacunar stroke [28, 29] as well as a –174G/C polymorphism of interleukin 6 [30, 31] and a gene variant of α 1 -antichymotrypsin – a plasma protease inhibitor [32]. …”
Section: Discussionmentioning
confidence: 99%
“…CSPG2 is both a component basement membrane [42] and was shown to be a direct target of p53 [43]. The SERPIN3A, which may be a causative of atherothrombotic infarction [44], was examined for decreased expression in the older age groups. Similarly, biphenyl hydrolase-like (BPHL), primarily expressed in liver and kidney, has a potential enzymatic role in detoxification processes, and was proposed to be reduced with age.…”
Section: Real-time Pcr Analysis Of Selected Genesmentioning
confidence: 99%
“…The levels of ACT are elevated in the serum of individuals with malignant disease. ACT has been detected in the nuclei of pancreas, stomach, breast, hepatic and lymphatic cancers despite not being present in the nucleus of normal tissues (48)(49)(50). Within these carcinomas, ACT has been shown to bind to DNA polymerase alpha and DNA primase, suggesting a role in protection against tumorigenesis by inhibiting DNA replication (48,50).…”
Section: Act In Human Diseasementioning
confidence: 99%
“…ACT has been detected in the nuclei of pancreas, stomach, breast, hepatic and lymphatic cancers despite not being present in the nucleus of normal tissues (48)(49)(50). Within these carcinomas, ACT has been shown to bind to DNA polymerase alpha and DNA primase, suggesting a role in protection against tumorigenesis by inhibiting DNA replication (48,50). Elevated serum ACT may be a potential biomarker for cancers of the pancreas (51), gastrointestinal tract (52) and lung (53).…”
Section: Act In Human Diseasementioning
confidence: 99%